Pola Asuh Positif Guru Dan Dampaknya Terhadap Pembentukan Konsep Diri Anak: Tinjauan Dari Perspektif Kurikulum Cinta - Syahrul Saputra; Hasnidar Rauna; Tuti Asriani; Sitti Fatimah SS (Prodi PIAUD STAI AL-GAZALI BONE, 2025)
Education plays an important role in shaping the foundation of children’s psychological development, particularly self-concept, which develops through social interactions with the closest environment. Teachers have a strategic role in this process due to the high intensity of their interactions with children in the school setting. This study aims to examine positive teacher parenting practices and their impact on the formation of early childhood self-concept from the perspective of the Love Curriculum (Kurikulum Cinta). This research employed a qualitative approach with a phenomenological study design. The research participants consisted of early childhood education teachers and children selected through purposive sampling at PAUD/TK institutions that implement the values of the Love Curriculum. Data were collected through participatory observation and in-depth interviews and analyzed using thematic analysis. The results indicate that positive teacher parenting is manifested through empathetic attitudes, warm communication, positive reinforcement, and guiding discipline. These practices contribute to the development of children’s positive self-concept, such as increased self-confidence, expressive courage, and emotional stability. The values of the Love Curriculum strengthen positive parenting practices by creating a safe and emotionally supportive learning environment. This study concludes that positive teacher parenting grounded in the Love Curriculum contributes significantly to the formation of early childhood self-concept.